The Analysis of Leading Plantation Sub-Sector Commodity Growth Centers in North Sumatra - Nurwenda Purba; La Ode Alwi; La Ode Kasno Arif (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
This study aims to find out the leading commodities in the plantation sub-sector in the district/city of North Sumatra Province, find out the competitiveness, growth, and progressivity of the plantation sub-sector commodity in the district/city of North Sumatra Province, and know the district/city of the plantation sub-sector which are the growth centers of the leading plantation sub-sector commodities in the districts/cities of North Sumatra Province. This research was conducted in North Sumatra Province from May 2021 to March 2022. The variable of this research is the production value of the plantation sub-sector commodity. Analysis of the data used in Location Quotient, Shift Share, and Klassen Typology analysis. This study indicates that The leading commodities in the plantation sub-sector are rubber, found in 14 districts/cities, followed by cocoa in 13 districts/cities, oil palm in 11 districts, coconut in 10 districts/cities, and arabica coffee in 9 districts. Cocoa is a competitive plantation sub-sector commodity with an area distribution in 21 districts/cities, followed by rubber in 16 districts/cities, oil palm and coconut in 13 districts, and arabica coffee in 6 districts. Meanwhile, commodity growth, coconut, and rubber quickly changed with regional distribution in 27 districts/cities, followed by arabica coffee in 12 regencies. And for commodity progressivity, coconut is a commodity that belongs to the progressive (advanced) group with an area distribution in 26 districts/cities, followed by rubber in 22 districts/cities, cocoa in 16 districts/cities, arabica coffee in 11 districts, and oil palm in 6 districts/city. The growth centers for the leading plantation sub-sector commodities in the districts/cities of North Sumatra Province are rubber, with an area distribution of 13 top districts/cities, followed by coconut in 9 leading districts/cities, arabica coffee in 8 leading districts, and cocoa in 7 leading districts/cities. At the same time, there are no leading districts/cities for oil palm.